The Role of Peers in Developing Social Intelligence Learners - Yuliani; Sugiarto, Hendro; Suheryawan, Undang (SAHUR Journal, 2023)
Adolescents frequently experience peer acceptance or rejection throughout their lives. Adolescents frequently imitate what their peer group does in order to escape rejection. The aim of this study was to determine how much peers contribute to kids' social intelligence development. A qualitative-descriptive research methodology was adopted. This qualitative method is a way to explore something to be studied and discover its meaning. Observation, interviews, and documentation studies were used as data gathering methods. The findings of this study suggest that kids' social interactions and intelligence will have a significant impact on their future accomplishments since one's social environment influences their ability to build positive relationships.